Combating cancer stem cells: RNA m6A methylation and small-molecule drug discovery - Zhang, Honghai; Wang, Xueer; Chen, Jianjun; Su, Rui (Frontiers in Drug Discovery, 2024)
Cancer stem cells (CSCs) are a small population of less differentiated cells with robust self-renewal ability. CSCs have been recognized as the root cause of tumor initiation, progression, relapse, and drug resistance. Recent studies from us and others have highlighted that N6-methyladenosine (m6A), the most prevalent modification in mRNA, plays a crucial role in carcinogenesis and CSC homeostasis. Dysregulation of the m6A modification machinery has been implicated in CSC survival and self-renewal, thereby regulating cancer progression and therapeutic resistance. In this review, we provide an overview of the roles and molecular mechanisms of the RNA m6A modification machinery in CSC survival and self-renewal. Additionally, we summarize the currently known small-molecule inhibitors targeting the dysregulated m6A modification machinery and discuss proof-of-concept studies focusing on the efficacy of these compounds in eliminating CSCs and cancers.